Evaluation of Various Shear-Thinning Models for Squalane Using Traction Measurements, TEHD and NEMD Simulations - Thomas Neupert; Dirk Bartel (Lubricants, 2023)
The accurate prediction of friction in highly loaded concentrated contacts is one of the most challenging aspects of thermal elastohydrodynamic (TEHD) simulation. The correct modelling of fluid behaviour on the macroscale, in particular non-Newtonian flow behaviour, is an essential prerequisite. For many years, shear-thinning models have been developed and validated with different approaches and controversially discussed. In basic research, model fluids are often used in this context, which have a similar behaviour to practical lubricants. Accompanied by earlier research results, this paper carries out comprehensive investigations on the rheometric behaviour of the model fluid squalane. Based on traction measurements at four different tribometers, an overall parameter optimisation and performance evaluation of three different shear-thinning models is performed using numerical TEHD simulations. In order to additionally validate the theoretical viscosity behaviour, the optimised shear-thinning curves are then compared with comprehensive non-equilibrium molecular dynamics (NEMD) simulations. The key aspect of this paper is the simultaneous consideration of the shear-thinning models in terms of rheometric, experimental, and simulative investigations without changing the parameters. All investigations show that the Eyring model, despite its simplicity, provides the best agreement in both the numerical contact simulation and the NEMD simulations.